Testing barrier materials in the development of a biosecurity pen to protect broilers against Campylobacter. (October 2021) - Greene, Genevieve; Koolman, Leonard; Whyte, Paul; Lynch, Helen; Coffey, Aidan; Lucey, Brigid; O'Connor, Lisa; Bolton, Declan
Abstract: Previous studies demonstrated that commercial broiler flocks could be protected from Campylobacter colonisation using a bird pen, termed the "biosecurity cube", constructed from four polycarbonate sheets (1m high x 2.5m long x 6 mm thick) supported at the corners by 4 × 1m high wooden columns. However, this design had issues with airflow and potential for upscaling. A biosecurity cube composed of four galvanised steel mesh panels (3.44m long x 1.25m high) was therefore developed onto which different barrier materials, preventing contact between the test birds and the main flock, were attached. The objective of this study was to test a range of barrier materials including cardboard, wire mesh, polyurethane film and later (at the suggestion of broiler industry personnel) flyscreen mesh. Initial studies suggested that while the cardboard and wire mesh were ineffective, the polyurethane film protected the birds. Further validation (over 2 separate trials, 7 cubes for each barrier material) demonstrated that polyurethane and flyscreen mesh were effective. It was concluded that a biosecurity pen infrastructure based on galvanised steel mesh panels surrounded by polyurethane film or flyscreen mesh was effective at protecting the birds from Campylobacter but upscaling studies will be undertaken before full implementation. Highlights: This study provides further evidence of biosecurity cube protection of broilers. A biosecurity cube framework could protect broilers from Campylobacter. Polyurethane and flyscreen barriers prevent Campylobacter colonisation.